PRINSIP DAN KRITERIA PERIKLANAN DARI PERSPEKTIF ISLAM - Teuku Meldi Kesuma (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2012)
Advertising in marketing Islamic products must be believed and understood as an important part of marketing based on Islam which should not be separated. This paper examines the principles and criteria of advertising from the perspective of Islam. It is caused by the increase of companies and institutions which are based on Islamic values such as Islamic financial institutions that promote its products the consumers. The important issues discussed in this paper is how the reality of concepts, principles, and criteria of Islamic advertising? Therefore this paper is developing an advertising concept from the perspective of Islam and to know for sure whether the principles and criteria that should exist in advertising Islam. The methodology applied in this paper is through a literature review by using content analysis. Hopefully, this study could develop an Islamic perspective advertisement concept in terms of principles and criteria. ======================================================================================================== Periklanan dalam memasarkan produk-produk Islam harus diyakini dan di pahami merupakan bahagian penting dalam pemasaran yang berdasarkan Islam yang tidak boleh dipisahkan. Tulisan ini mengkaji prinsip-prinsip dan kriteria periklanan dalam perspektif Islam. Hal ini disebabkan semakin ramai dan tingginya pertumbuhan perusahaan dan institusi yang berlandaskan nilai-nilai Islam seperti institusi keuangan Islam yang mempromosikan produk dan perkhidmatannya kepada orang ramai. Persoalan penting yang dibahas dalam kertas kerja ini adalah bagaimanakah bentuk konsep, prinsip dan kriteria periklanan Islam yang sebenarnya? Oleh karena itu tujuan kertas kerja ini adalah untuk membangun satu konsep periklanan dari perspektif Islam dan untuk mengenal pasti apakah prinsip-prinsip serta kriteria yang seharusnya ada dalam periklanan Islam. Metodologi kajian yang digunakan dalam kertas kerja ini adalah metode kepustakaan dengan menggunakan analisis isi. Kajian ini diharapkan dapat membentuk konsep periklanan dalam perspektif Islam dari segi prinsip dan kriterianya.